2022
DOI: 10.1108/dprg-11-2021-0152
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of telework on work performance in public services: experiences during the COVID-19 pandemic

Abstract: Purpose Telework has been widely used during the COVID-19 pandemic. However, distance work performed through teleworking may hinder organisational operations in public services owing to lower-than-expected work performance. This research paper aims to explore how teleworking relates to work performance and flexibility during the COVID-19 pandemic. Design/methodology/approach The sample included 178 managers and employees in public services. The relationships between the variables were evaluated using linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Performance is also positively linked to the intention to continue teleworking and employee engagement (Ameen et al 2023). On the other hand, it is also reported that few employees perceive that their performance matters (Lopes Júnior and Daniel 2022) or that it helps them to improve (Varotsis 2022a). As a result of mandatory teleworking from home, performance eroded (Magnier-Watanabe et al 2022) and the extensive use of teleworking systems also negatively affected this outcome (Kuruzovich et al 2021).…”
Section: Outcomes Related To Workmentioning
confidence: 99%
“…Performance is also positively linked to the intention to continue teleworking and employee engagement (Ameen et al 2023). On the other hand, it is also reported that few employees perceive that their performance matters (Lopes Júnior and Daniel 2022) or that it helps them to improve (Varotsis 2022a). As a result of mandatory teleworking from home, performance eroded (Magnier-Watanabe et al 2022) and the extensive use of teleworking systems also negatively affected this outcome (Kuruzovich et al 2021).…”
Section: Outcomes Related To Workmentioning
confidence: 99%
“…On the other hand, one of the most widely accepted understandings of telework points to the accumulation of several factors, such as work being done somewhere else than the physical location of the company, and the usage of technical devices and software equipment [53]. A 14-year span analysis [54] shows that the chronology of concepts related to telework includes terms such as teleworking, homeworking, virtual work, telework, distributed work, telecommuting, and remote working.…”
Section: Work Performance In the Context Of Post-covid Work Arrangementsmentioning
confidence: 99%
“…This classification is of great use to our study because, in the context of working from a distance, sometimes employees lose contact with the ancillary activities of their job descriptions, so they need additional abilities such as autonomy and flexibility. Nevertheless, remote and hybrid work performance have begun to be interesting study topics with promising results [54,57].…”
Section: Work Performance In the Context Of Post-covid Work Arrangementsmentioning
confidence: 99%
“…For example, soft skill acquisition and training methodology in Malaysian private companies significantly predict employee work performance (Ibrahim et al, 2017). During the pandemic of COVID-19, telework had different impacts on work performance in Greek public services, and information and communication technologies (ICTs) based on task-technology fit can make employees from different countries feel less lonely even when working at home and generate high performance in their tasks (Abelsen, et al, 2023;Varotsis, 2022). Researchers focusing on work performance in China are mainly from business schools of universities, with such hotspots of work performance research as work engagement, organizational identity, innovative performance, etc.…”
Section: Work Performancementioning
confidence: 99%